2000
DOI: 10.1111/j.1545-5300.2000.39203.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision Making among Family Therapists and Individual Therapists*

Abstract: In this study, we investigated the ethical decision making of 30 individual and 30 family therapists in order to detect the types of decision making used by practicing therapists. Informants responded to three ethical dilemmas. Two of the situations were hypothetical. The third dilemma was a situation the informant had experienced in practice. Each interview was assessed for decision-making style, using content analysis. Kohlberg's justice reasoning and Gilligan's care reasoning provided the conceptual foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Ethical guidelines have been criticized for neglecting the ethical conflicts or competing interests arising from different system levels of individual versus family (Newfield et al ., 2000) and it has been suggested that a process ethics needs to be established (Gergen, 2001; Swim et al ., 2001). We welcome these ideas and wish to point out that ethical considerations cannot be based only on evaluations concerning existing practices where indirect or decontextualized methods are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical guidelines have been criticized for neglecting the ethical conflicts or competing interests arising from different system levels of individual versus family (Newfield et al ., 2000) and it has been suggested that a process ethics needs to be established (Gergen, 2001; Swim et al ., 2001). We welcome these ideas and wish to point out that ethical considerations cannot be based only on evaluations concerning existing practices where indirect or decontextualized methods are used.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of moral reasoning in couple and family therapy (Newfield et al ., 2000; Wall et al ., 1999) approach the issue methodologically from a position external to actual therapeutic situations. They either focus on moral conflicts at the level of theory (cf.…”
mentioning
confidence: 99%
“…They followed the ethics of caring as described by Gilligan and Attanucci (1988) in which ethical behavior arises from the needs of others in specific relationship contexts. This orientation takes into account the consequences of a decision for all involved, how the relationships would be affected, the importance of avoiding hurt, and altruism (Newfield et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They are held accountable for nursing decision-making regarding certain problems for certain patients [7]. Ethical decision-making should be applied as an organized form of ethical thoughtfulness for solving the ethical conflicts [8]. Nurses as professional individuals should be familiar with the ethical decisionmaking and they should respect patients' ethical rights without risking their own conscience [7,9].…”
Section: Introductionmentioning
confidence: 99%